2004
DOI: 10.1159/000081718
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation Potential of FDCPmix Cells following Injection into Blastocysts

Abstract: Factor-dependent cell Paterson mixed potential (FDCPmix) cells are murine, multipotent, interleukin-3 (IL-3)-dependent progenitor cells, established from long-term bone marrow cultures. They show multilineage myeloid/erythroid and osteoclast differentiation capacity in vitro. FDCPmix cells are neither immortalised, leukaemic nor transformed and have no detectable karyotypic abnormalities. To investigate the broader differentiation potential of FDCPmix cells in vivo, they were injected into murine blastocysts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…Optimal transplantation approach and time When hUCB-derived CD34 + cells [18] , human acute myeloid leukemia cells [17] and mouse FDCPmix cells (murine progenitor cells of haematopoietic origin; Petrovic et al [21] ) were microinjected into murine blastocysts, respectively, they preferentially engrafted in PB and yolk sac of embryos, and less frequently detected in other tissues of embryos or adults.…”
Section: Multiorgan Engraftment and Unevenly Distribution Of Donor-dementioning
confidence: 99%
“…Optimal transplantation approach and time When hUCB-derived CD34 + cells [18] , human acute myeloid leukemia cells [17] and mouse FDCPmix cells (murine progenitor cells of haematopoietic origin; Petrovic et al [21] ) were microinjected into murine blastocysts, respectively, they preferentially engrafted in PB and yolk sac of embryos, and less frequently detected in other tissues of embryos or adults.…”
Section: Multiorgan Engraftment and Unevenly Distribution Of Donor-dementioning
confidence: 99%
“…Since the potential of BMSCs to differentiate into hepatocytes was first demonstrated [Petersen et al, 1999], the capacity of BMSCs to differentiate into liver cells has been validated repeatedly [Avital et al, 2001[Avital et al, , 2002Petrovic et al, 2004;Grompe, 2005]. Furthermore, several recent reports have shown that HPCs can be derived from BMSCs [Theise et al, 2000;Thorgeirsson and Grisham, 2006].…”
Section: Discussionmentioning
confidence: 99%
“…No report exists in the literature about successful tetraploid complementation with somatic stem cells. Somatic stem cells can form chimeras when combined with normal (but not tetraploid) embryos and they then show their plasticity by contributing to the formation of various organs and tissues (the high plasticity reported in Clarke et al 39 has been debated by other groups 40 and seems to depend considerably on the cell type). The formation of a whole embryo or living animal from somatic stem cells by tetraploid complementation has not been reported in the literature and does not seem to be possible.…”
Section: Direct Cloning By Tetraploid Complementationmentioning
confidence: 99%